Occupational health and safety management system in the prevention of psychosocial risks in the workers of the liaison office of the Ministry of Development and Social Inclusion in the city of Tacna - period 2015. - Lipa Portugal, Diana Irma (2018)
Objective: The objective of the field research in the area of Public Policies was to determine if the occupational health and safety management system affects the prevention of psychosocial risks in the workers of the liaison office of the Ministry of Development and Social Inclusion in the city of Tacna-period 2015. The design was descriptive, not experimental. The sample was constituted by the workers of the liaison office of the Ministry of Development and Social Inclusion in the city of Tacna-Periodo, 2015, with the totality of 18 workers. The instrument used was the questionnaire. The results determined that the occupational health and safety management system affects the prevention of psychosocial risks in the workers of the liaison office of the Ministry of Development and Social Inclusion in the city of Tacna - 2015 period, according to the statistical test Coefficient of Spearman Rho is 0.720.